2010
DOI: 10.1177/1947601910388937
|View full text |Cite
|
Sign up to set email alerts
|

The "Mutated in Colorectal Cancer" Protein Is a Novel Target of the UV-Induced DNA Damage Checkpoint

Abstract: MCC is a potential tumor suppressor gene, which is silenced by promoter hypermethylation in a subset of colorectal cancers. However, its functions have remained poorly understood. In the present study, we describe a novel function of MCC in the DNA damage response. Several novel phosphorylation sites were identified by mass spectrometry, including 2 highly conserved ATM/ATR consensus sites at serine 118 and serine 120. In addition, exposure to ultraviolet radiation (UV), but not phleomycin, caused PI3K-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 32 publications
2
44
3
Order By: Relevance
“…In addition, Mcc localizes to the leading edge of polarized cells and interacts in a PDZ-independent manner with the contractile protein myosin IIB (Pangon et al, 2012). Knockdown of MCC impairs lamellipodia formation and cell migration in Boyden chamber assays (Arnaud et al, 2009;Pangon et al, 2010Pangon et al, , 2012. Lastly, we recently observed enriched MCC expression in a microarray screen comparing the differentiation of human embryonic stem cells in response to combinations of TGFβ-related growth factors (Teo et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…In addition, Mcc localizes to the leading edge of polarized cells and interacts in a PDZ-independent manner with the contractile protein myosin IIB (Pangon et al, 2012). Knockdown of MCC impairs lamellipodia formation and cell migration in Boyden chamber assays (Arnaud et al, 2009;Pangon et al, 2010Pangon et al, , 2012. Lastly, we recently observed enriched MCC expression in a microarray screen comparing the differentiation of human embryonic stem cells in response to combinations of TGFβ-related growth factors (Teo et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…In overexpression studies, MCC was shown to physically associate with β-catenin in the nucleus to negatively regulate canonical TCF/ LEF-dependent Wnt signaling and to inhibit cell proliferation (Fukuyama et al, 2008;Matsumine et al, 1996). More recently, MCC was observed to be mainly localized in the cytoplasm of colon cancer cell lines but translocated to the nucleus in response to DNA damage to induce cell cycle arrest (Pangon et al, 2010). These findings are consistent with the frequent hypermethylation (and gene silencing) of the MCC promoter in human CRCs (Kohonen-Corish et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to regulating cell proliferation in many cancer cell lines [17,26], it has been suggested that MCC is involved in differentiation [27], epithelial cell migration [28,29], DNA damage response [30] and inhibition of NFB activation [31,32] or Wnt signalling [17]. Importantly, the tumour suppressor role of MCC has been confirmed in a mouse model of colon cancer [33].…”
Section: Discussionmentioning
confidence: 98%